2015
DOI: 10.1017/jfm.2015.637
|View full text |Cite
|
Sign up to set email alerts
|

Transient force augmentation due to counter-rotating vortex ring pairs

Abstract: Of particular significance to biological locomotion is vortex ring interaction. In the wakes of animals, this unsteady process determines the changes in the impulse of counter-rotating vortex ring pairs (VRPs), which consist of two vortex rings with opposite sense of rotation. In this paper, these VRPs are proposed to be of particular importance to unsteady force generation. We carry out numerical computations, simulating the piston-cylinder apparatus, to study the transient changes in the impulse of counter-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Recently, it has been shown that these interactions at the interface of vortices can enhance thrust (Fu and Liu, 2015). However, this effect is highly dependent on vortex spacing (Fu and Liu, 2015) and is controlled by the local vorticity conditions (Stanaway et al, 1988).…”
Section: Hydrodynamic Effects Of Interactions Between Adjacent Vorticesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been shown that these interactions at the interface of vortices can enhance thrust (Fu and Liu, 2015). However, this effect is highly dependent on vortex spacing (Fu and Liu, 2015) and is controlled by the local vorticity conditions (Stanaway et al, 1988).…”
Section: Hydrodynamic Effects Of Interactions Between Adjacent Vorticesmentioning
confidence: 99%
“…However, this effect is highly dependent on vortex spacing (Fu and Liu, 2015) and is controlled by the local vorticity conditions (Stanaway et al, 1988). We argue that, by maintaining a constant distance between adjacent vortices, the bending kinematics of the control lampreys controlled the interaction of the adjacent vortices, whose circulation grew as they traveled toward the tail but whose spacing was kept constant.…”
Section: Hydrodynamic Effects Of Interactions Between Adjacent Vorticesmentioning
confidence: 99%
“…Although this was not measured in our study, the bending of the snake’s body was observed in our video recordings suggesting that the angular velocity of the snake’s body plays a role in the creation of body vortices in addition to the change of direction of its oscillation. The production of counter-rotating vortex tubes along the body has been suggested to generate additional trust (Fu and Liu 2015) during swimming.…”
Section: Discussionmentioning
confidence: 99%